Perbandingan Performansi Algoritme Kriptografi Advanced Encryption Standard (AES) dan Blowfish pada Text di Platform Android - Muhammad Taufiqur Rahman; Aryo Pinandito; Eko Sakti Pramukantoro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
To create an Android application, developers need to consider things other than security, such as application performance, because Android itself as a mobile device inherently has limited resources so that efforts to improve the performance of applications developed specifically for the Android platform needs to be done. Questions on developer forums such as Stackoverflow on which algorithms are performing better on Android platforms are emerging, to answer those questions there will be a performance comparison between two well-known and popularly used cryptographic algorithms, AES and Blowfish. The study chose two popular symmetric cryptography algorithms that are used: Advanced Encryption Standard (AES) algorithms and Blowfish algorithms to compare performance on the Android operating system. The data used derived from the generator data based on certain rules. Comparison of performance will be done with 3 parameters, namely: data length, key length, and differences in processor architecture. Testing each data is done 20 times to improve the accuracy of algorithmic performance. The test results show that the Blowfish algorithm has better encryption and decryption performance than the AES algorithm on testing of data length and key length, on testing of Intel AES processor is superior to 0.3-0.4 ms faster while on ARM processor Blowfish is faster by 0.2 Ms.